Numerical simulation of local cooling on residual stress and deformation of welded joints of unequal thickness plates - Yang He; Zhidong Yang; Dongdong Yang; Ruihai Duan; Jiangmin Xu; Wenqin Wang; Mingxiao Shi; Guoxiang Xu; Shujin Chen (Journal of Materials Research and Technology)
To address the significant variations in stress distribution and welding deformation of unequal thickness plate welded joints, this study investigates the effect of local cooling on residual stress and welding deformation through experiments and numerical simulations. A three-dimensional thermo-elasto-plastic finite element model was developed and validated against temperature field measurements and weld cross-sectional profiles. Comparative analyses of simulated and experimentally measured welding stresses and deformations reveal that local cooling significantly reduces tensile stress in the weld zone while promoting a more uniform stress distribution in the heat-affected zone. The implementation of local cooling on the thin plate expands the regions of compressive stress at both ends of the weld and increases transverse tensile stress near the weld and within the cooled zone. Compared to the non-cooled condition, the treated specimens exhibit markedly improved welding stress distribution and reduced deformation. Angular distortion decreases by 18 % on the thin-plate side and 26.7 % on the thick-plate side, concurrently suppressing buckling deformation. These findings demonstrate that local cooling not only enhances deformation resistance in unequal thickness welded joints but also favorably modifies the magnitude and distribution patterns of welding stress. This study provides theoretical and technical guidance for controlling stress and deformation in unequal thickness plate welded joints.